Flavonoids Accumulation in Fruit Peel and Expression Profiling of Related Genes in Purple (Passiflora edulis f. edulis) and Yellow (Passiflora edulis f. flavicarpa) Passion Fruits - Meng Shi (MDPI AG, 2021)
Flavonoids play a key role as a secondary antioxidant defense system against different biotic and abiotic stresses, and also act as coloring compounds in various fruiting plants. In this study, fruit samples of purple (Passiflora edulis f. edulis) and yellow (Passiflora edulis f. flavicarpa) passion fruit were collected at five developmental stages (i.e., fruitlet, green, veraison, maturation, and ripening stage) from an orchard located at Nanping, Fujian, China. The contents of flavonoid, anthocyanin, proanthocyanin, and their metabolites were determined using ultra-performance liquid chromatography-mass spectrometry (UPLC-MS), activities of key enzymes involved in flavonoid metabolism were measured, and expression profiling of related genes was done using quantitative real-time PCR (qRT-PCR). The results revealed that total flavonoids, anthocyanins, and procyanidins were found to be increased in the fruit peel of both cultivars with fruit maturity. Total flavonoids, anthocyanins, procyanidins, flavonoid metabolites (i.e., rutin, luteolin, and quercetin), and anthocyanin metabolites (i.e., cyanidin-3-O-glucoside chloride, peonidin-3-O-glucoside, and pelargonidin-3-O-glucoside) were found abundant in the peel of purple passion fruit, as compared to yellow passion fruit. Principle component analysis showed that the enzymes, i.e., C4H, 4CL, UFGT, and GST were maybe involved in the regulation of flavonoids metabolism in the peel of passion fruit cultivars. Meanwhile, PePAL4, Pe4CL2,3, PeCHS2, and PeGST7 may play an important role in flavonoid metabolism in fruit peel of the passion fruit. This study provides new insights for future elucidation of key mechanisms regulating flavonoids biosynthesis in passion fruit.